PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PELAKSANAAN SISTEM PENJAMINAN MUTU PENDIDIKAN - Nilawati Nilawati; Sumadi Sumadi; Sulton Djasmi (Program Studi Magister Manajemen Pendidikan)
This study aimed to describe: (1) LPMP of Lampung Province strategy in building human resource capacity in accordance with the demands of Quality Assurance System of Education; (2) the impact of human resource development in the work culture in LPMP Lampung, and (3) the perspective of human resource development in LPMP in the future. This study uses a phenomenological qualitative approach. Data were collected through interviews, documentation and observation. Results from this study are: (1) LPMP strategy of Lampung Province in building human capacity is by developing program / activity plans, and analyzes the factors that support and hinder the development of human resource capacity; (2) the impact of human resource development in the work culture in LPMP Lampung Province is a change in the form of knowledge (cognitive) like the principles, procedures, and processes of education; (3) the perspective of human resource development in LPMP of Lampung province is that this institution has a commitment in quality improvement.Penelitian ini bertujuan untuk mendeskripsikan: (1) strategi LPMP Provinsi Lampung dalam membangun kapasitas SDM sesuai dengan tuntutan Sistem Penjaminan Mutu Pendidikan; (2) dampak dari pengembangan SDM pada budaya kerja di LPMP Lampung, dan (3) perspektif pengembangan SDM di LPMP Lampung di masa depan. Penelitian ini menggunakan metode pendekatan kualitatif fenomenologis. Data dikumpulkan melalui wawancara, dokumentasi dan observasi. Hasil dari penelitian ini adalah: (1) strategi LPMP Provinsi Lampung dalam membangun kapasitas manusia adalah dengan perencanaan program / kegiatan, dan menganalisis faktor-faktor yang mendukung dan menghambat perkembangan SDM; (2) dampak dari pengembangan SDM pada budaya kerja di LPMP Provinsi Lampung adalah perubahan dalam bentuk pengetahuan (kognitif) seperti prinsip, prosedur, dan proses pendidikan; (3) perspektif pengembangan SDM di LPMP Provinsi Lampung adalah lembaga ini memiliki komitmen terhadap peningkatan kualitas.Kata kunci: pengembangan, penjaminan mutu pendidikan, sumber daya manusia